The Influence of Knowledge of Islamic Economics on Interest in Investing in Sharia Stocks among Generation Z in Surakarta City with the UTAUT Model - Aji, Cakrabumi Sumarsono; Achiria, Siti (Unisia, 2023)
Sharia-compliant investments are gaining traction among younger generations, particularly in Indonesia, where Generation Z represents a significant demographic with growing interest in ethical financial products. This study aims to explore the factors influencing Behavioral Intention to invest in Sharia-compliant stocks by integrating Islamic economic knowledge and the Unified Theory of Acceptance and Use of Technology (UTAUT) constructs, including Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. A quantitative methodology was employed, utilizing a structured survey distributed to 100 respondents in Surakarta, Indonesia. Multiple linear regression analysis was conducted to assess the relationships between independent variables and Behavioral Intention. Supporting assumption tests, such as normality, multicollinearity, autocorrelation, and heteroskedasticity, confirmed the validity and reliability of the regression model. The results revealed that Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions significantly and positively influence Behavioral Intention. However, Islamic economic knowledge did not exhibit a statistically significant effect, indicating that practical and social factors outweigh theoretical understanding in driving investment decisions. The model explained 49.3% of the variance in Behavioral Intention, highlighting the importance of usability, perceived benefits, and social dynamics in shaping Generation Z’s preferences. These findings underscore the need for targeted strategies that emphasize user-friendly platforms, ethical value alignment, and community-driven promotion to enhance participation in Sharia-compliant investments. By addressing these factors, financial institutions and policymakers can foster financial inclusivity and promote sustainable economic growth.